PENGARUH DAYA DUKUNG LAHAN DAN PERTUMBUHAN EKONOMI SEKTOR PERTANIAN TERHADAP PENDAPATAN PETANI JAGUNG - Marisa Sutanty; Abdul Rahim; Dewi Sulastri (Pusat Riset dan Publikasi, 2021)
This study aims to know the effect of land capacity and agricultural economic growth sector toward the income of Batu Bangka Village community. The type of this study was Associative. The data source used was primary data.The population in this study were all farmers who run corn farming business. The number of samples were 71 of corn farmers. Data collection techniques used was questionnaires. The analysis tool uses the SPSS application. The analysis technique used was multiple linear regression. The results of study showed that partially land capacity and economic growth had an effect toward income. This was based on the t-value of land capacity variable toward income with t-value of 2.611> t-table of 1.668 with a significant value of 0.005 <0.05 and t-value of the economic growth variable toward income of 2.879> t-table of 1.668 with significant value of 0.005 <0, 05, while the value of f-value was 7.909 > f-table of 3.13 with a significance value of 0.001 < 0.05. The value of the coefficient of determination was 0.189, it means that the percentage of land capacity and economic growth toward income was 18.9%.